Every job is a sales job : how to use the art of selling to win at work - McGovern, Cindy (McGraw-Hill, 2020)
An essential roadmap to achieving professional and personal success-from the "First Lady of Sales" While you may not have "sales" in your title, that doesn't mean you don't have to sell. Renowned sales authority Dr. Cindy McGovern believes that everyone is a salesperson, regardless of his or her job description. When you ask for a referral, network to form a new connection, or interview for a job, you're selling the other person on an ideal version of yourself. Every Job is a Sales Job will help you learn to identify "selling" opportunities that you may have overlooked. This indispensable roadmap will show you how to take control of your personal and professional success. McGovern shares her proven 5-step sales process to help you attract new business, retain existing customers, and spot opportunities to promote yourself and your ideas. You'll learn how to: •Create a plan and set attainable goals •Identify subtle opportunities that could result in future success •Establish trust and listen for clues to understand what others need •Ask for what you want and move past the fear of rejection •Follow up on your ask, be grateful, and pay it forward •Muster up the courage to ask for referrals and references.